2015
DOI: 10.1111/jce.12718
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Clinical Outcome of Premature Interruption of Cryoenergy Delivery Due to Phrenic Nerve Palsy During Second Generation Cryoballoon Ablation for Paroxysmal Atrial Fibrillation

Abstract: Conclusion: Our findings show that patients in whom freezing was interrupted due to PNP had a similar outcome on 1-year follow-up compared with those in whom freezing cycles were completed in the septal veins. No baseline clinical or procedural characteristics were found to predict AF recurrence in patients having experienced PNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
11
2
Order By: Relevance
“…There were five studies involving only paroxysmal AF patients, two studies involving only persistent AF patients, and eight studies involving both types of AF. As for ablation strategy, eight studies adopted the “bonus” strategy, two studies adopted the “no‐bonus” strategy, three studies adopted both strategies, and the remaining two studies did not provide sufficient information on their ablation strategies. Although several studies were carried out by the same authors' groups, we ruled out the possibility of patient groups duplication based on study methods and patient characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were five studies involving only paroxysmal AF patients, two studies involving only persistent AF patients, and eight studies involving both types of AF. As for ablation strategy, eight studies adopted the “bonus” strategy, two studies adopted the “no‐bonus” strategy, three studies adopted both strategies, and the remaining two studies did not provide sufficient information on their ablation strategies. Although several studies were carried out by the same authors' groups, we ruled out the possibility of patient groups duplication based on study methods and patient characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported the clinical success rates of patients with paroxysmal AF. PVI with CB‐2G resulted in a 1‐year clinical success rate of 82% (95% CI: 79–86%) in paroxysmal AF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of PNI has been reported to increase from 2‐11% in the first‐generation balloon to 3‐24% in the second‐generation balloon . Previous study showed that the mean time to PNI was 123.6 ± 47 s (median: 131), indicating that shorter application duration might prevent the occurrence of this complication …”
Section: Discussionmentioning
confidence: 99%